Digital technology and the expansion of outdoor experience in outdoor activities - Hajo Schuurman (Current Issues in Sport Science)
Introduction After the outbreak of covid-pandemic, the digital age has been highlighted in society, where the divide between indoors and outdoors (and work and private life) has both intensified and blurred. It has become more pronounced as daily life increasingly unfolds within a finely tuned digital infrastructure, making venturing outdoors less taken for granted. At the same time, digital technologies disrupt this infrastructure, causing the boundary between indoors and outdoors to fade. Especially in outdoor activities, digital tools like smartphones, GPS systems, and sports apps have become deeply embedded in the experience of being outdoors. These technologies are no longer mere accessories to outdoor activities, they have become indispensable to how we orient and navigate in natural areas (Kennedy at al. 2024). Still, the outdoor experience also has a certain allure, prompting people to take a break from their smartphones (Helms et al., 2019). For individuals, questions about being outdoors, such as to what extent they rely on digital infrastructures, have become central. People engage with digital technologies in diverse ways, from fully embracing them (complexification) to removing their presence (simplification). This research proposes a conceptual framework for understanding the intersection of technology and outdoor experiences, focusing on how these technologies shape, support, or challenge our relationship with nature.